Efektivitas Bakteri Asam Laktat Terhadap Percepatan Dekomposisi Bahan Organik Mucuna Dalam Proses Fermentasi Kompos - Zainal, Zainal Abidin; Hidayat, Nur; Rusmini, Rusmini; La Mudi, La Mudi; Dwi Mentari, F. Silvi; Budi Arifiana, Nisa; Krismiratsih, Fitri (Universitas Muhammadiyah Sorong, 2025)
This study aims to determine the effect of using Lactic Acid Bacteria (LAB) isolates on the fermentation process of mucuna-based compost. The parameters observed included temperature, pH, color, aroma, and texture for 27 days of fermentation. The results showed that LAB treatment had a significant effect on the acceleration and quality of fermentation results. The temperature increased faster and remained within the optimal range of microbial activity (22–55°C). The pH value decreased in the early fermentation phase due to the production of organic acids, then returned to being stable approaching neutral at the end of fermentation. The color change towards blackish brown occurred faster in the LAB treatment, indicating earlier compost maturity than the control. The odorless aroma appeared earlier (day 9) in the LAB treatment compared to the control (day 12), and the texture became smoother faster. Overall, the use of LAB isolates was proven to accelerate the decomposition process of mucuna organic materials, increase microorganism activity, and produce compost with better quality than without LAB treatment.